Two new species of isospora (Apicomplexa: Eimeriidae) from geckoes of the genus Rhacodactylus (Sauria: Gekkonidae) endemic to New Caledonia - Modrý, David; Jirků, Miloslav; Veselý, Milan (Folia parasitologica, 2004)
Coprological examination of New Caledonian geckoes of the genus Rhacodactylus Fitzinger, 1843 revealed two new species of coccidia. Isospora leachiani sp. n. from R. leachianus (Cuvier, 1829) has oval, colourless oocysts, measuring 21-26 x 16-18.5 microm. Sporocysts are ellipsoidal, 11-12.5 x 6.5-8 microm, with distinct Stieda and substieda bodies. Oocysts of Isospora sykorai sp. n. from R. ciliatus (Guichenot, 1866) are elongately oval to cylindrical, 20-23.5 x 11-14 microm; sporocysts of this species are ellipsoidal, 10-11.5 x 7-8 microm, with a slightly pointed end and Stieda and substieda bodies. Infected geckoes did not exhibit any alteration of their health status.
Keywords: Animals; oocysty; New Caledonia; ještěři; Oocysts; Female; zvířata; feces; Nová Kaledonie; Feces; Isospora; Lizards; ženské pohlaví; interferenční mikroskopie; Microscopy, Interference